Kontribusi Pondok Pesantren Hidayatullah Bagi Masyarakat Palangka Raya - Hikmah, Hikmah; Hartati, Zainap (Universitas Islam Sultan Agung, 2021)
Pondok Pesantren is a unique Islamic religious education institution. Pesantren as the oldest Islamic education system in Indonesia, socio-religious institutions, and educational vehicles for Muslims who want to explore religious knowledge. Pesantren is a center for the study and exploration of the treasures of Islamic knowledge and the center of the da'wah movement to spread Islam in Indonesia. This study uses a qualitative descriptive method, namely collecting data and drawing conclusions. The Hidayatullah Islamic Boarding School was founded by Ustadz Anwar Timumun at the end of 1995, he pioneered da'wah in Bumi Tambun Bungai, Palangkaraya City. The concept of Hidayatullah Islamic Boarding School education is based on monotheism, with education levels from PAUD, SD and SMP to create a generation of intelligent, pious and monotheisticKeywords: History, Islamic Boarding School Development, Hidayatullah Islamic Boarding School